Immersive Art as Gesamtkunstwerk in Contemporary Museum: Artistic and Curatorial Practice - Kiseleva, Evgeniya I. (Actual Problems of Theory and History of Art, 2020)
Aspirations to see a sound, to hear a color and to touch a word were impulses for the great inventionsin art of the 19th and 20th centuries. However, at that time, lots of experiments with new art forms and synthesis of arts took place away from of museums, constrained with rules and orders. In the course of the 20th century, the transformation of museums’ borders was particularly connected with the development of immersive art. Enriching immersive and sensory experience in the museum is one of key concepts that defined the transformation of the museum and its engagement with its audience in the 20th and 21st centuries. The changes in the image, role, and functions of the museum in the post-informational society are mainly connected with the development of immersive art and with the shift from the concept of “looking and thinking”to the concept of “feeling and participating”. The multiplicity of connotations of “immersion” presents difficulties for the definition of immersive artworks today. The present article deals with immersive and somatic experiences in contemporary museum in the historical context. The paper traces connections between the concepts of immersion, non-visual art perception and affect theory. The article describes museums projects where sound, smell, touch and proprioception build immersive experiences. The text also informs about the development of immersive art practices and the idea of an exhibition as “total artwork” in historical contextof Gesamtkunstwerk concept.
Keywords: immersion; multisensory art; Gesamtkunstwerk; total artwork; synthesis of arts; installation; contemporary art; museology; display